The relationship between TQM and project performance: Empirical evidence from Malaysian construction industry - Jong, C.; Sim, Khoon; Lew, T. (2019)
© 2019, © 2019 The Author(s). This open access article is distributed under a Creative Commons Attribution (CC-BY) 4.0 license. Many studies have suggested the adaptation and implementation of Total Quality Management (TQM) is likely to improve an organization’s performance. A considerable amount of literature has examined the relationship between TQM and other elements like business performance, organizational performance, and marketing performance in different industries. However, little is known of the influence of TQM in project performance in the context of Malaysian construction organizations. The objective of the study is to examine the relationship between TQM and project performance in Malaysian construction organizations. Data were collected from member list of companies from the Construction Industry Development Board (CIDB) Malaysia. A total of 161 valid responses has been returned for data analysis. The findings revealed that TQM practices were partially correlated with project performance of Malaysian construction organizations. Specifically, operation focus and workforce focus were perceived as dominant TQM practices on project performance. This study contributes to the knowledge on TQM and project performance by providing empirical evidence on their ability to improve Malaysian construction industry. Besides, this study provides further insight for industrial practitioners to understand the roles of TQM and its ability in enhancing project performance.